“Spin‐Rinse and Repeat”: Facile Processing to Improve Cytocompatibility of Poly(3,4‐Ethyelenedioxythiophene): Polystyrene Sulfonate Composites for Bioelectronics - Joshua Killilea; Aaron Lee; Estelle A. Cuttaz; Giovanni Carlo Miceli; Leire L. Suquia; Josef A. Goding; Christopher A. R. Chapman; Rylie A. Green (Advanced NanoBiomed Research)
Conductive polymers, such as poly(3,4‐ethyelenedioxythiophene):polystyrene sulfonate (PEDOT:PSS), offer exciting prospects in organic bioelectronic applications. Translation of commercially available formulations of PEDOT:PSS is hampered by leachable contaminants. Herein, a facile processing technique utilizing differences in polymer–solvent affinity and centrifugation of poor dispersions of PEDOT:PSS to remove leachable components is presented. 1H‐nuclear magnetic resonance spectroscopy of the centrifugation supernatant identifies PSS as the most abundant impurity removed. To demonstrate versatility and applicability to bioelectronic applications, centrifuged PEDOT:PSS is blended with medical grade polyurethane. Bulk composite swelling and degradation are largely unaltered, and the electrochemical performance of the composite is not significantly compromised. Marked improvement in cytocompatibility is only observed in composites fabricated using centrifugation, indicating that soluble components such as PSS contribute significantly to cytotoxicity. Removal of excess PSS improves the ability of these polymer systems to act as drug delivery vehicles as evidenced by differences in chemotherapeutic efficacy of doxorubicin following electrophoretic release. It is demonstrated that excess PSS in commercial formulations can exert significant cytotoxicity, and its reduction can produce cytocompatible PEDOT:PSS materials for use across a wide spectrum of bioelectronic applications.